Enhancing Prospective Elementary School Teachers' 4C Skills: Instrument Development in the Context of Materials and Changes Lecture - Yusup Maulana; Wahyu Sopandi; Rahmat Iqbal; Maryos Ipaubla (Jurnal Ilmiah Sekolah Dasar, 2024)
This research is driven by the urgent need to ensure that prospective elementary school teachers possess adequate 4C skills (Communication, Collaboration, Critical Thinking, and Creativity) to meet the challenges of 21st-century education, particularly in the context of materials and changes lectures. The purpose of this study was to develop and validate a 4C skills instrument for prospective elementary school teachers in lectures on the topic of matter and its changes. The approach used was quantitative with a survey design involving 400 elementary school teacher education students in Indonesia. The sample selection was based on simple random sampling technique. Findings from the PLS-SEM analysis of the measurement model showed that the convergent validity test value through factor loading for communication skills (CMC), collaboration (CLB), critical thinking (CTC), creativity (CTV), and lecturer assignments (C) showed values greater than 0.6 and and the Average Variance Extracted (AVE) value showed values greater than 0.5. The Reliability test value through the composite Reliability (CR) value for each variable shows a value greater than 0.7 and the Cronbach's Alpha value shows a value greater than 0.6. Based on this value, the instrument is declared valid and reliable so that the instrument can be used.